Prof. Dr. Dennis von Heimburg — Deep Plane Facelift — Frankfurt - von Heimburg, Dennis (DEEPPLANE™, 2026)
Surgeon profile record for Prof. Dr. Dennis von Heimburg, practicing in Frankfurt, Germany. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003101; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; germany; frankfurt